Downstream research results of pineapple extract as a disinfectant for PKK Tarai Bangun Village, Riau - Siti Juariah; Alfin Surya; Sukri Sukri; Wahyu Margi Sidoretno; Wahyu Ramadhan; Reiz Mutia AR (Universitas Muhammadiyah Magelang, 2022)
This service activity is a downstreaming of research results by involving PKK in making soap from pineapple weevil extract (waste from pineapple processing). The purpose of this activity is to create entrepreneurs and improve the welfare of the community. Service activities are carried out with the debriefing method regarding the knowledge and skills of making antibacterial dish soap, packaging, product marketing. The results of this program are that the community can produce antibacterial dish soap, increase community welfare, and the formation of MSMEs.